Absolute parameters of young stars: V454 Carinae. Issue 2 (20th September 2018) - Butland, R J; Erdem, A; Özkardeş, B; Blackford, M G; Sürgit, D; Budding, E; Demircan, O
ABSTRACT: We present combined photometric and spectroscopic analyses of the multiple star V454 Carinae. High-resolution spectra of the system were taken at the University of Canterbury Mt. John Observatory during the years 2008-18. These have been processed using generic and purpose-built software. New digital single lens reflex photometry of the system has also been collected and similarly analysed. Absolute parameters for the three main stars confirm V454 Car's young and near-Main-Sequence nature. We find: M 1  = 4.6 ± 0.4, M 2  = 4.4 ± 0.4, M 3  = 4.5 ± 0.5, R 1  = 2.83 ± 0.18, R 2  = 2.74 ± 0.16, R 3  = 2.78 ± 0.16 (⊙); T 1 ∼ 17 500, T 2 ∼ 15 500, T 3 ∼ 15 000 (K), age ∼30 Myr, photometric distance ∼500 (pc). The major component V454 Car A is the close binary identified by the HIPPARCOS satellite. This binary and component B appear to be in eccentric orbits about a common centre of gravity with a period of ∼1900 d. Analysis of the radial velocity curves suggests that the mass of component B is greater than that of its visible member. Measured radial velocities of this visible star show irregularities with a time-scale of about a week. The galactic location, proper motions, and age of V454 Car support the runaway nature proposed by others, and the combined results are consistent with a dynamical ejection scenario from the Vela region of Gould's Belt relatively soon after the stars' formation.